Genetic variations in TAS2R3 and TAS2R4 bitterness receptors modify papillary carcinoma risk and thyroid function in Korean females. Issue 1 (December 2018) - Choi, Jeong-Hwa; Lee, Jeonghee; Yang, Sarah; Lee, Eun; Hwangbo, Yul; Kim, Jeongseon
Abstract Type 2 taste receptors (T2Rs, TAS2Rs ) mediate bitterness perception and are involved in diverse defence mechanisms in extraoral tissues. The thyrocyte-expressed T2Rs control thyroid hormone production, and this regulatory role may be associated with susceptibility to thyroid diseases. This study examined whether the variations inTAS2Rs modify the risk of papillary thyroid carcinoma (PTC) and whether such T2R-related PTC risk is associated with genetically modified thyroid function. We conducted a case-control study with 763 Korean females, including 250 PTC cases. Seventy-three single-nucleotide polymorphisms in 13TAS2R genes and the pre-diagnosis levels of 4 thyroid-related functional markers [total triiodothyronine (TT3), free thyroxine, thyroid-stimulating hormone and thyroglobulin] were analysed. Individuals withTAS2R3/4 CC haplotype (rs2270009 and rs2234001) were at a lower risk for PTC than those with the remaining haplotypes (odds ratio = 0.59, 95% confidence interval: 0.36–0.97). Furthermore, TT3 levels were significantly reduced forTAS2R3/4 CC haplotype carriers compared with other haplotype carriers (p = 0.005). No other genetic variants exhibited critical associations with the PTC phenotype and biomarkers. In summary, genetic variations in T2R3/4 bitterness receptors may modify the PTC risk, and the genetically modified thyroid hormone level by those variations may be linked with the PTC-T2Rs association.